Visual Rhetoric of Ultra Milk X ITZY Advertisement on Youtube Media - Chairini Aisyah; Handriyotopo Handriyotopo (Green Publisher Indonesia, 2024)
The advertising industry in Indonesia currently uses many brand ambassadors from South Korea. Ads that use visualizations from South Korea are effective in increasing sales of local products and the image of these products. The purpose of this study is to analyze the meaning of messages and visual images displayed by advertisements in campaigning #DontStopYourMove in collaboration with Korean idols ITZY on YouTube social media for the younger generation. This research uses a critical paradigm through descriptive qualitative research methods to identify data and analyze the visual text of advertisements with observation steps through scenes in advertisements. This research uses the rhetorical triangle approach and the AISAS Model communication flow. This research aims to interpret the meaning of the message in the advertisement and analyze the visual image and analyze the audience's activity of interest in the Ultra Milk advertisement to see the position of the advertisement and ITZY brand ambassador who promotes Ultra Milk milk products and campaigns #DontStopYourMove. The results of this study show (1) The meaning of Ultra Milk's advertising message is for young people who have a lot of activities to consume milk as a nutritional companion, becoming a generation that